PENDAMPINGAN PENASIHAT HUKUM TERHADAP TERDAKWA BERDASARKAN PASAL 56 KUHAP: Assistance of Legal Counsel to the Defendant Based on Article 56 of the Criminal Procedure Code - Batubara, Atikah Salsa; Hadjar, Abdul Ficar (AMICUS CURIAE, 2024)
Assistance by legal counsel is a right for all defendants, including defendants who are threatened with a sentence of more than 5 years. The formulation of the problem raised is about the judge's consideration in examining the defendant at the trial of a criminal case which carries a sentence of more than 5 (five) years imprisonment without the assistance of legal counsel and the legal consequences of the decision handed down to the defendant in a criminal case which carries a sentence of more than 5 (five) years and was examined, decided without the assistance of legal counsel. This research method applies a type of research based on normative research referring to seikundeir data. The nature of the research is descriptive and the analysis of conclusions uses a deuctive method. The results of the research and discussionThe actions of the defendant who deliberately took the life of another person and was sentenced to 13 years imprisonment without the assistance of legal counsel, then the conclusion of this study, looking at the decision of the Supreme Court which then became procedural law, explained that if the defendant was not accompanied by legal counsel, all legal products produced were null and void and contained legal defects.